Nano-silver coating for low-temperature and high-humidity unfreezing equipment and preparation method of nano-silver coating
By preparing modified graphite-loaded nanosilver wires and isocyanate-based terminal polyurethane prepolymers, combined with polyurethane acrylate and polyacrylate, the problems of insufficient antibacterial, scratch resistance and low temperature stability of nanosilver coatings in the prior art are solved, and high-quality coating preparation is achieved.
Patent Information
- Application Number
- CN202411699843.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-11-26
AI Technical Summary
The existing nanosilver coatings for low-temperature and high-humidity thawing equipment have shortcomings in antibacterial properties, scratch resistance and low-temperature stability, and the dispersion and compatibility problems of functional additives and nanosilver in the coating matrix lead to a decrease in the coating quality.
Nanosilver A and nanosilver B were prepared, which were graphite-loaded nanosilver wires, modified with sodium oleate to improve dispersion and compatibility; Nanosilver B was nanosilver particles prepared with isocyanate-based blocked polyurethane prepolymer as template agent, combined with polyurethane acrylate and polyacrylate, and added photoinitiator to form a high-quality coating.
The good antibacterial properties, low temperature resistance and scratch resistance of nanosilver coatings have been achieved. Due to the excellent dispersion and compatibility of nanosilver A and nanosilver B, the mechanical properties and low temperature stability of the coating have been significantly improved, avoiding performance degradation.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coatings, and specifically discloses a nano silver coating for low-temperature and high-humidity thawing equipment and a preparation method thereof. Background Art
[0002] When nanosilver coating is used in low-temperature and high-humidity thawing equipment, it has the following advantages: Nanosilver has broad-spectrum antibacterial properties, and can inhibit the growth of Gram-negative bacteria, Gram-positive bacteria and other bacteria by releasing silver ions, which can effectively prevent microbial contamination and maintain the freshness and nutritional content of meat; and the synthesis method of nanosilver is green and environmentally friendly, which can reduce the impact on the environment.
[0003] In addition to excellent antibacterial properties, nanosilver coatings for low-temperature and high-humidity thawing equipment also require good scratch resistance and good low-temperature environment stability to extend the service life of the equipment; therefore, in the prior art, functional additives are often added to nanosilver coatings, or nanosilver, coating substrates, etc. are modified; however, problems such as the dispersibility and compatibility of functional additives and nanosilver in the coating matrix often lead to a decrease in coating quality; in summary, it is of great significance to study a nanosilver coating for low-temperature and high-humidity thawing equipment with good antibacterial properties, scratch resistance, and low-temperature resistance, and a preparation method thereof, in order to obtain a coating with stable quality. Summary of the invention
[0004] The object of the present invention is to provide a nano silver coating for low-temperature and high-humidity thawing equipment and a preparation method thereof, so as to solve the problems raised in the prior art.
[0005] To achieve the above object, the present invention provides the following technical solution: A method for preparing a nano silver coating for low temperature and high humidity thawing equipment: comprising the following steps: S1: dissolving sodium oleate in water, introducing ammonia, heating the oil bath to 45-55°C, adding graphite-loaded nano silver wires, keeping warm and stirring, filtering, washing, and drying to obtain a sodium oleate modified filler; S2: Take acrylic acid, methyl methacrylate, methyl acrylate, allyl trimethyl ammonium chloride, hydroxyethyl methacrylate, styrene, butyl acrylate, and di-tert-amyl peroxide, and disperse them evenly to obtain a mixed monomer; Take di-tert-amyl peroxide, vinyl silicone oil, and sodium oleate modified filler, add a mixed solvent and stir evenly, heat to 140-145°C and keep warm for 20-30 minutes, drop the mixed monomer, cool to 80-85°C, add ethanedithiol and azobisisobutyronitrile, keep warm for 2-3 hours, remove the solvent, and obtain nanosilver A; S3: Take isocyanate-terminated polyurethane prepolymer as template, adjust pH to 4-6, add AgNO3 aqueous solution, stir evenly, and then drop ascorbic acid under inert gas protection to obtain nanosilver B; S4: Take polyurethane acrylate, polyacrylate, acetone, photoinitiator, nanosilver A, and nanosilver B, mix them evenly, and obtain nanosilver coating.
[0006] More optimally, the nano silver coating comprises the following raw materials, calculated by weight: 20-25 parts of polyurethane acrylate, 15-20 parts of polyacrylate, 30-40 parts of acetone, 0.1-0.2 parts of photoinitiator, 1-2 parts of nano silver A, and 1-2 parts of nano silver B.
[0007] More optimally, the sodium oleate modified filler comprises the following raw materials, by weight: 0.4-0.6 parts of sodium oleate, 200-400 parts of water, 4-6 parts of graphite-supported nanosilver wires; More optimally, the mixed monomer comprises the following raw materials, by mass: 6-8 parts of acrylic acid, 2-3 parts of methyl methacrylate, 2-3 parts of methyl acrylate, 4-5 parts of allyltrimethylammonium chloride, 8-10 parts of hydroxyethyl methacrylate, 3-4 parts of styrene, 10-12 parts of butyl acrylate, and 1-3 parts of di-tert-amyl peroxide; The vinyl silicone oil has a molecular weight of 500 and a vinyl content of 8%; The nanosilver A comprises the following raw materials, by mass: 6-8 parts of acrylic acid, 2-3 parts of methyl methacrylate, 2-3 parts of methyl acrylate, 4-5 parts of allyltrimethylammonium chloride, 8-10 parts of hydroxyethyl methacrylate, 3-4 parts of styrene, 10-12 parts of butyl acrylate, 80-100 parts of a mixed solvent, 8-12 parts of vinyl silicone oil, 80-100 parts of sodium oleate modified filler, 0.5-0.8 parts of ethanedithiol, and 0.2-0.3 parts of azobisisobutyronitrile; The mixed solvent is diethylene glycol butyl ether and dipropylene glycol butyl ether in a mass ratio of 1:1.
[0008] More optimally, in the nanosilver B, the mass ratio of the template, ascorbic acid and silver nitrate is (20-30): (8-10): (1-2).
[0009] More optimally, the preparation of the isocyanate-terminated polyurethane prepolymer includes the following steps: taking polyethylene glycol, castor oil, dihydroxybenzoic acid, trimethylolpropane, and acetone, stirring evenly, adding isophorone diisocyanate and triphenylmethane triisocyanate after the temperature reaches 68-70°C, adding a tin catalyst dropwise, stirring for 3-4 hours, and obtaining an isocyanate-terminated polyurethane prepolymer.
[0010] More optimally, the isocyanate-terminated polyurethane prepolymer includes the following raw materials, calculated by mass: 13 to 15 parts of polyethylene glycol, 3 to 4 parts of castor oil, 2 to 3 parts of dihydroxybenzoic acid, 2 to 3 parts of trimethylolpropane, 25 to 30 parts of acetone, 10 to 12 parts of isophorone diisocyanate, 4 to 6 parts of triphenylmethane triisocyanate (4,4ˊ,4〞-triphenylmethane triisocyanate), and 0.2 to 0.4 parts of tin catalyst (dibutyltin dilaurate).
[0011] More optimally, the preparation of the polyurethane acrylate includes the following steps: taking an isocyanate-terminated polyurethane prepolymer, heating it to 60-70°C, adding hydroxyethyl methacrylate, stirring the reaction until the -NCO content reaches the theoretical end point, stopping the reaction, and removing the solvent by rotary evaporation to obtain polyurethane acrylate.
[0012] More optimally, the polyurethane acrylate comprises the following raw materials, calculated by weight: 10 to 15 parts of isocyanate-terminated polyurethane prepolymer and 2 to 3 parts of hydroxyethyl methacrylate.
[0013] More optimally, the preparation of the graphite-loaded silver nanowires includes the following steps: adding graphite to ethanol, uniformly dispersing by ultrasonication, and obtaining a graphite dispersion; heating the graphite dispersion to 150-160° C. for 10-15 min, adding polyvinyl pyrrolidone, heating for 20-30 min, adding 0.2 mmol / L CuCl2 aqueous solution and 0.2 mmol / L AgNO3 aqueous solution, stirring for 5-8 min, adding 3 mmol / L AgNO3 aqueous solution, stirring for 20-30 min, filtering, washing, and drying to obtain graphite-loaded silver nanowires; The graphite dispersion includes the following raw materials, calculated by weight: 2 to 3 parts of graphite and 150 to 200 parts of ethanol; the graphite-loaded nanosilver wires include the following raw materials, calculated by weight: 100 parts of graphite dispersion, 2 to 3 parts of polyvinyl pyrrolidone, 10 to 12 parts of 0.2 mmol / L CuCl2 aqueous solution, 20 to 25 parts of 0.2 mmol / L AgNO3 aqueous solution, and 10 to 15 parts of 3 mmol / L AgNO3 aqueous solution.
[0014] Preferably, the curing conditions of the nano silver coating are: temperature 45-55°C, 800-1000 mj / cm 2 Expose to ultraviolet light until film is formed.
[0015] Compared with the prior art, the beneficial effects achieved by the present invention are as follows: a nano silver coating is prepared, comprising polyurethane acrylate, polyacrylate, photoinitiator, nano silver A and nano silver B; wherein the nano silver A is a modified graphite-loaded nano silver wire, the nano silver wire grown with graphite as the base point has more excellent dispersion stability, and the graphite can improve the mechanical properties of the coating; the graphite-loaded nano silver wire is treated with sodium oleate to improve the dispersibility and introduce a double bond that can participate in the next reaction, and then it is modified with an acrylic mixed monomer and vinyl silicone oil, wherein styrene improves the waterproof effect of the coating, and allyl trimethyl ammonium chloride and nano silver work together to improve the antibacterial effect, and the silicone oil has a low surface tension and can play a leveling agent effect, and has good flexibility at low temperatures, thereby improving the low temperature stability of the coating; the nano silver A modified by the above method has good antibacterial and low temperature resistance, and has good compatibility with the polyurethane acrylate and polyacrylate in the coating; Nanosilver B is a nanosilver particle prepared by using isocyanate-terminated polyurethane prepolymer as a template. Compared with nanosilver wire, nanosilver powder has better antibacterial performance. Therefore, nanosilver A and nanosilver B are used together to simultaneously improve the mechanical properties and antibacterial properties of the coating. The nanosilver particles prepared by using the template with a hyperbranched structure have uniform particle size and good dispersion stability, and the polyurethane acrylate in the coating is also prepared by using the isocyanate-terminated polyurethane prepolymer as a raw material. The two have similar structures and improved compatibility. The polyurethane structure has good wear resistance, which is conducive to improving scratch resistance. At the same time, due to the presence of castor oil, the mechanical properties and low-temperature stability of the coating are also improved. In summary, the nano silver coating prepared by the present invention has excellent mechanical properties, good scratch resistance, good antibacterial property and low-temperature stability. Since nano silver A and nano silver B have good compatibility with polyurethane acrylate and polyacrylate, when used in combination according to the formula of the present invention, the performance degradation caused by problems such as dispersibility is greatly reduced; after the nano silver coating is irradiated with ultraviolet light, it is further cross-linked under the action of a photoinitiator to obtain a coating with excellent quality. DETAILED DESCRIPTION
[0016] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0017] The following parts are by mass unless otherwise specified; Preparation method of graphite-loaded silver nanowires: take 3 parts of graphite, add 180 parts of ethanol, and disperse uniformly by ultrasonication to obtain a graphite dispersion; take 100 parts of the graphite dispersion, heat to 160°C for 15 minutes, add 3 parts of polyvinyl pyrrolidone, heat for 20 minutes, add 12 parts of 0.2 mmol / L CuCl2 aqueous solution and 25 parts of 0.2 mmol / L AgNO3 aqueous solution, stir for 5 minutes, add 15 parts of 3 mmol / L AgNO3 aqueous solution, stir for 30 minutes, filter, wash, and dry to obtain graphite-loaded silver nanowires; Example 1: S1: Take 0.5 parts of sodium oleate and dissolve it in 300 parts of water, stir and dissolve, introduce ammonia, heat the oil bath to 50°C, add 5 parts of graphite-supported nanosilver wires, keep warm and stir for 20 minutes, vacuum filter, wash, and dry to obtain a sodium oleate modified filler; S2: Take 8 parts of acrylic acid, 2 parts of methyl methacrylate, 2 parts of methyl acrylate, 5 parts of allyltrimethylammonium chloride, 9 parts of hydroxyethyl methacrylate, 4 parts of styrene, 10 parts of butyl acrylate, and 2 parts of di-tert-amyl peroxide, and disperse them evenly to obtain a mixed monomer; 100 parts of mixed solvent, 0.4 parts of di-tert-amyl peroxide, 10 parts of vinyl silicone oil, and 90 parts of sodium oleate modified filler were added to a reaction kettle, and the temperature was raised to 145° C. and kept warm for 30 minutes. The mixed monomer was added dropwise. After the addition was completed, the reaction kettle was cooled to 80° C., 0.6 parts of ethanedithiol and 0.3 parts of azobisisobutyronitrile were added, and the temperature was kept warm for 3 hours. The solvent was removed to obtain nanosilver A; S3: Add 13 parts of polyethylene glycol, 4 parts of castor oil, 3 parts of dihydroxybenzoic acid, 3 parts of trimethylolpropane, and 30 parts of acetone to a three-necked flask equipped with a polytetrafluoroethylene stirring rod, a condenser, and a nitrogen conduit, stir evenly, add 11 parts of isophorone diisocyanate and 5 parts of triphenylmethane triisocyanate after the temperature reaches 70°C, add 0.3 parts of dibutyltin dilaurate dropwise, stir for 4 hours, and obtain an isocyanate-terminated polyurethane prepolymer; S4: Take isocyanate-terminated polyurethane prepolymer as template, adjust pH to 5, add 0.1 mol / L AgNO3 aqueous solution, stir evenly, and slowly drop ascorbic acid under inert gas protection to obtain nanosilver B; the mass ratio of template, ascorbic acid and silver nitrate is 25:8:1; S5: Take 12 parts of isocyanate-terminated polyurethane prepolymer, raise the temperature to 65° C., add 3 parts of hydroxyethyl methacrylate, stir and react until the -NCO content reaches the theoretical end point, stop the reaction, and remove the solvent by rotary evaporation to obtain polyurethane acrylate; S6: Take 22 parts of polyurethane acrylate, 18 parts of polyacrylate, 40 parts of acetone, 0.2 parts of photoinitiator, 1.5 parts of nanosilver A, and 2 parts of nanosilver B, mix them evenly to obtain nanosilver coating.
[0018] Example 2: S1: Take 0.4 parts of sodium oleate and dissolve it in 300 parts of water, stir and dissolve, introduce ammonia, heat the oil bath to 50°C, add 4 parts of graphite-supported nanosilver wires, keep warm and stir for 20 minutes, vacuum filter, wash, and dry to obtain a sodium oleate modified filler; S2: Take 6 parts of acrylic acid, 3 parts of methyl methacrylate, 2 parts of methyl acrylate, 5 parts of allyltrimethylammonium chloride, 8 parts of hydroxyethyl methacrylate, 4 parts of styrene, 10 parts of butyl acrylate, and 3 parts of di-tert-amyl peroxide, and disperse them evenly to obtain a mixed monomer; 100 parts of mixed solvent, 0.4 parts of di-tert-amyl peroxide, 8 parts of vinyl silicone oil, and 80 parts of sodium oleate modified filler were added to a reaction kettle, the temperature was raised to 145° C. and kept warm for 30 minutes, and the mixed monomer was added dropwise. After the addition was completed, the reaction kettle was cooled to 80° C., 0.6 parts of ethanedithiol and 0.3 parts of azobisisobutyronitrile were added, and the temperature was kept warm for 3 hours. The solvent was removed to obtain nanosilver A; S3: Add 15 parts of polyethylene glycol, 4 parts of castor oil, 2 parts of dihydroxybenzoic acid, 2 parts of trimethylolpropane, and 30 parts of acetone to a three-necked flask equipped with a polytetrafluoroethylene stirring rod, a condenser, and a nitrogen conduit, stir evenly, add 10 parts of isophorone diisocyanate and 6 parts of triphenylmethane triisocyanate after the temperature reaches 70°C, add 0.3 parts of dibutyltin dilaurate dropwise, stir for 4 hours, and obtain an isocyanate-terminated polyurethane prepolymer; S4: Take isocyanate-terminated polyurethane prepolymer as template, adjust pH to 5, add 0.1 mol / L AgNO3 aqueous solution, stir evenly, and then slowly drop ascorbic acid under inert gas protection to obtain nanosilver B; the mass ratio of template, ascorbic acid and silver nitrate is 20:8:1; S5: Take 10 parts of isocyanate-terminated polyurethane prepolymer, raise the temperature to 65° C., add 2 parts of hydroxyethyl methacrylate, stir and react until the -NCO content reaches the theoretical end point, stop the reaction, and remove the solvent by rotary evaporation to obtain polyurethane acrylate; S6: Take 20 parts of polyurethane acrylate, 20 parts of polyacrylate, 40 parts of acetone, 0.2 parts of photoinitiator, 2 parts of nanosilver A, and 1 part of nanosilver B, mix them evenly to obtain nanosilver coating.
[0019] Example 3: S1: Take 0.6 parts of sodium oleate and dissolve it in 300 parts of water, stir and dissolve, introduce ammonia, heat the oil bath to 50°C, add 6 parts of graphite-supported nanosilver wires, keep warm and stir for 20 minutes, vacuum filter, wash, and dry to obtain a sodium oleate modified filler; S2: Take 8 parts of acrylic acid, 2 parts of methyl methacrylate, 3 parts of methyl acrylate, 4 parts of allyltrimethylammonium chloride, 80 parts of hydroxyethyl methacrylate, 4 parts of styrene, 10 parts of butyl acrylate, and 2 parts of di-tert-amyl peroxide, and disperse them evenly to obtain a mixed monomer; 100 parts of mixed solvent, 0.4 parts of di-tert-amyl peroxide, 12 parts of vinyl silicone oil, and 100 parts of sodium oleate modified filler were added to a reaction kettle, and the temperature was raised to 145° C. and kept warm for 30 minutes. The mixed monomer was added dropwise. After the addition was completed, the reaction kettle was cooled to 80° C., 0.6 parts of ethanedithiol and 0.3 parts of azobisisobutyronitrile were added, and the temperature was kept warm for 3 hours. The solvent was removed to obtain nanosilver A; S3: Add 13 parts of polyethylene glycol, 3 parts of castor oil, 3 parts of dihydroxybenzoic acid, 3 parts of trimethylolpropane, and 30 parts of acetone to a three-necked flask equipped with a polytetrafluoroethylene stirring rod, a condenser, and a nitrogen conduit, stir evenly, add 12 parts of isophorone diisocyanate and 4 parts of triphenylmethane triisocyanate after the temperature reaches 70°C, add 0.3 parts of dibutyltin dilaurate dropwise, stir for 4 hours, and obtain an isocyanate-terminated polyurethane prepolymer; S4: Take isocyanate-terminated polyurethane prepolymer as template, adjust pH to 5, add 0.1 mol / L AgNO3 aqueous solution, stir evenly, and slowly add ascorbic acid under inert gas protection to obtain nanosilver B; the mass ratio of template, ascorbic acid and silver nitrate is 30:10:2; S5: Take 15 parts of isocyanate-terminated polyurethane prepolymer, raise the temperature to 65° C., add 3 parts of hydroxyethyl methacrylate, stir and react until the -NCO content reaches the theoretical end point, stop the reaction, and remove the solvent by rotary evaporation to obtain polyurethane acrylate; S6: Take 25 parts of polyurethane acrylate, 15 parts of polyacrylate, 40 parts of acetone, 0.2 parts of photoinitiator, 1 part of nanosilver A, and 2 parts of nanosilver B, mix them evenly to obtain nanosilver coating.
[0020] Comparative Example 1 (changing the addition ratio of nanosilver A and nanosilver B, and the other method steps are consistent with Example 1): Take 22 parts of polyurethane acrylate, 18 parts of polyacrylate, 40 parts of acetone, 0.2 parts of photoinitiator, 0.5 parts of nanosilver A, and 3 parts of nanosilver B, mix them evenly to obtain a nanosilver coating.
[0021] Comparative Example 2 (changing the addition ratio of nanosilver A and nanosilver B, and the other method steps are consistent with Example 1): Take 22 parts of polyurethane acrylate, 18 parts of polyacrylate, 40 parts of acetone, 0.2 parts of photoinitiator, 3 parts of nanosilver A, and 0.5 parts of nanosilver B, mix them evenly, and obtain a nanosilver coating.
[0022] Comparative Example 3 (the preparation methods of nanosilver A and nanosilver B were changed, and the remaining steps were the same as those of Example 1): S1: 0.5 parts of sodium oleate were dissolved in 300 parts of water, stirred to dissolve, ammonia was introduced, and an oil bath was heated to 50° C., 5 parts of graphite-supported nanosilver wires were added, the mixture was kept warm and stirred for 20 minutes, vacuum filtered, washed, and dried to obtain a sodium oleate-modified filler A; Take 0.5 parts of sodium oleate and dissolve it in 300 parts of water, stir and dissolve, introduce ammonia, heat to 50°C in an oil bath, add 5 parts of granular nanosilver, keep warm and stir for 20 minutes, vacuum filter, wash and dry to obtain sodium oleate modified filler B; S2: Take 8 parts of acrylic acid, 2 parts of methyl methacrylate, 2 parts of methyl acrylate, 5 parts of allyltrimethylammonium chloride, 9 parts of hydroxyethyl methacrylate, 4 parts of styrene, 10 parts of butyl acrylate, and 2 parts of di-tert-amyl peroxide, and disperse them evenly to obtain a mixed monomer; add 100 parts of a mixed solvent, 0.4 parts of di-tert-amyl peroxide, 10 parts of vinyl silicone oil, and 90 parts of sodium oleate modified filler A in a reaction kettle, heat to 145°C and keep warm for 30 minutes, add the mixed monomer dropwise, and after the addition is complete, cool the reactor to 80°C, add 0.6 parts of ethanedithiol and 0.3 parts of azobisisobutyronitrile, keep warm for 3 hours, remove the solvent, and obtain intermediate A; Take 8 parts of acrylic acid, 2 parts of methyl methacrylate, 2 parts of methyl acrylate, 5 parts of allyltrimethylammonium chloride, 9 parts of hydroxyethyl methacrylate, 4 parts of styrene, 10 parts of butyl acrylate, and 2 parts of di-tert-amyl peroxide, and disperse them evenly to obtain a mixed monomer; add 100 parts of a mixed solvent, 0.4 parts of di-tert-amyl peroxide, 10 parts of vinyl silicone oil, and 90 parts of sodium oleate modified filler B in a reaction kettle, heat to 145°C and keep warm for 30 minutes, add the mixed monomer dropwise, and after the addition is complete, cool the reaction kettle to 80°C, add 0.6 parts of ethanedithiol and 0.3 parts of azobisisobutyronitrile, keep warm for 3 hours, and remove the solvent to obtain an intermediate B; S3: Add 13 parts of polyethylene glycol, 4 parts of castor oil, 3 parts of dihydroxybenzoic acid, 3 parts of trimethylolpropane, and 30 parts of acetone to a three-necked flask equipped with a polytetrafluoroethylene stirring rod, a condenser, and a nitrogen conduit, stir evenly, add 11 parts of isophorone diisocyanate and 5 parts of triphenylmethane triisocyanate after the temperature reaches 70°C, add 0.3 parts of dibutyltin dilaurate dropwise, stir for 4 hours, and obtain an isocyanate-terminated polyurethane prepolymer; S4: Take 3 parts of isocyanate-terminated polyurethane prepolymer, heat to 65°C, add 10 parts of intermediate A, stir and react for 4 hours, stop the reaction, and remove the solvent by rotary evaporation to obtain nanosilver A; Take 3 parts of isocyanate-terminated polyurethane prepolymer, heat to 65°C, add 10 parts of intermediate B, stir and react for 4 hours, stop the reaction, and remove the solvent by rotary evaporation to obtain nanosilver B; S5: Take 12 parts of isocyanate-terminated polyurethane prepolymer, raise the temperature to 65° C., add 3 parts of hydroxyethyl methacrylate, stir and react until the -NCO content reaches the theoretical end point, stop the reaction, and remove the solvent by rotary evaporation to obtain polyurethane acrylate; S6: Take 22 parts of polyurethane acrylate, 18 parts of polyacrylate, 40 parts of acetone, 0.2 parts of photoinitiator, 1.5 parts of nanosilver A, and 2 parts of nanosilver B, mix them evenly to obtain nanosilver coating.
[0023] Comparative Example 4 (changing the addition ratio of polyurethane acrylate and polyacrylate, the other method steps are consistent with Example 1): Take 12 parts of polyurethane acrylate, 28 parts of polyacrylate, 40 parts of acetone, 0.2 parts of photoinitiator, 1.5 parts of nanosilver A, and 2 parts of nanosilver B, mix them evenly to obtain a nanosilver coating.
[0024] In the above examples, the test methods used are conventional methods unless otherwise specified; the raw materials used are commercially available unless otherwise specified, and the sources of the raw materials are as follows: graphite (expanded graphite 150 mesh, Henan Huawen Chemical Co., Ltd.); ethanol (CAS: 64-17-5); polyvinyl pyrrolidone (S30268, Shanghai Yuanye); sodium oleate (S30245, Shanghai Yuanye); acrylic acid (CAS: 79-10-7); methyl methacrylate (CAS: 80-62 -6); methyl acrylate (CAS: 96-33-3); allyl trimethyl ammonium chloride (S70384, Shanghai Yuanye); hydroxyethyl methacrylate (CAS: 868-77-9); styrene (CAS: 100-42-5); butyl acrylate (CAS: 141-32-2); di-tert-amyl peroxide (CAS: 10508-09-5); diethylene glycol butyl ether (CAS: 112-34-5); dipropylene glycol butyl ether (CAS: 35884-42- 5); vinyl silicone oil (molecular weight 500, vinyl content 8%, Shanghai Jiader Chemical Technology Co., Ltd.); ethanedithiol (CAS: 540-63-6); azobisisobutyronitrile (CAS: 78-67-1); polyethylene glycol (polyethylene glycol 1000, Shanghai Fangye Chemical Co., Ltd.); castor oil (S24344, Shanghai Yuanye); dihydroxybenzoic acid (CAS: 99-10-5); trimethylolpropane (CAS: 77-99-6); acetone (CAS: 67 -64-1); isophorone diisocyanate (CAS: 4098-71-9); 4,4ˊ,4〞-triphenylmethane triisocyanate (CAS: 2422-91-5); dibutyltin dilaurate (CAS: 77-58-7); ascorbic acid (CAS: 50-81-7); photoinitiator (photoinitiator 1173, CAS: 7473-98-5); particulate nanosilver (ABZW-12-5, Biotech); polyacrylate (TX2216, Yingxin).
[0025] Experiment: Take the nano silver coatings prepared in Examples 1 to 3 and Comparative Examples 1 to 4; (1) put them into a well-sealed container with a volume of 0.5 L, seal them and place them in an environment of -100°C to observe whether there are abnormal phenomena such as agglomeration, stratification and precipitation; (2) apply them on a standard steel plate with a thickness of 0.1 mm; and at a temperature of 50°C and a concentration of 1000 mj / cm 2 Drying under ultraviolet light to form a film to obtain a sample; refer to GB21551.2-2010 to determine the antibacterial rate; (3) Refer to standard GB / T9279-2007 (scratch tester) to test the scratch resistance of the sample; the load weight is 150g; specific data are shown in the table below;
[0026] Conclusion: Comparative Examples 1 and 2 change the addition ratio of nanosilver A and nanosilver B, and the performance is not as good as that of the embodiment, from which it can be seen that the addition amount of the two nanosilver needs to be controlled; Comparative Example 3 changes the preparation method of nanosilver A and nanosilver B, and due to problems such as grafting rate, the performance is not as good as that of the embodiment; Comparative Example 4 changes the addition ratio of polyurethane acrylate and polyacrylate, and the scratch resistance is significantly reduced, from which it can be seen the importance of their addition amount; In summary, the nanosilver coating prepared by the present invention has good antibacterial properties, low temperature resistance, and scratch resistance.
[0027] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
Claims
1. A method for preparing a nano silver coating for low-temperature and high-humidity thawing equipment, characterized in that: The following steps are involved: S1: Sodium oleate is dissolved in water, ammonia is introduced, the oil bath is heated to 45-55°C, graphite-loaded nanosilver wires are added, the mixture is stirred at the temperature, filtered, washed, and dried to obtain a sodium oleate modified filler; S2: Take acrylic acid, methyl methacrylate, methyl acrylate, allyl trimethyl ammonium chloride, hydroxyethyl methacrylate, styrene, butyl acrylate, and di-tert-amyl peroxide, and disperse them evenly to obtain a mixed monomer; Take di-tert-amyl peroxide, vinyl silicone oil, and sodium oleate modified filler, add a mixed solvent and stir evenly, heat to 140-145°C and keep warm for 20-30 minutes, drop the mixed monomer, cool to 80-85°C, add ethanedithiol and azobisisobutyronitrile, keep warm for 2-3 hours, remove the solvent, and obtain nanosilver A; S3: Take isocyanate-terminated polyurethane prepolymer as template, adjust pH to 4-6, add AgNO3 aqueous solution, stir evenly, and then drop ascorbic acid under inert gas protection to obtain nanosilver B; S4: Take polyurethane acrylate, polyacrylate, acetone, photoinitiator, nanosilver A, and nanosilver B, mix them evenly, and obtain nanosilver coating.
2. The method for preparing a nano silver coating for low-temperature and high-humidity thawing equipment according to claim 1, characterized in that: The nano silver coating comprises the following raw materials, calculated by weight: 20-25 parts of polyurethane acrylate, 15-20 parts of polyacrylate, 30-40 parts of acetone, 0.1-0.2 parts of photoinitiator, 1-2 parts of nano silver A, and 1-2 parts of nano silver B.
3. The method for preparing a nano silver coating for low-temperature and high-humidity thawing equipment according to claim 1, characterized in that: The sodium oleate modified filler comprises the following raw materials, calculated by weight: 0.4-0.6 parts of sodium oleate, 200-400 parts of water, and 4-6 parts of graphite-supported nanosilver wires; The nanosilver A comprises the following raw materials, calculated by mass: 6-8 parts of acrylic acid, 2-3 parts of methyl methacrylate, 2-3 parts of methyl acrylate, 4-5 parts of allyltrimethylammonium chloride, 8-10 parts of hydroxyethyl methacrylate, 3-4 parts of styrene, 10-12 parts of butyl acrylate, 80-100 parts of a mixed solvent, 8-12 parts of vinyl silicone oil, 80-100 parts of sodium oleate modified filler, 0.5-0.8 parts of ethanedithiol, and 0.2-0.3 parts of azobisisobutyronitrile.
4. The method for preparing a nano silver coating for low-temperature and high-humidity thawing equipment according to claim 1, characterized in that: In the nanosilver B, the mass ratio of the template, ascorbic acid and silver nitrate is (20-30): (8-10): (1-2).
5. The method for preparing a nano silver coating for low-temperature and high-humidity thawing equipment according to claim 1, characterized in that: The preparation of the isocyanate-terminated polyurethane prepolymer comprises the following steps: taking polyethylene glycol, castor oil, dihydroxybenzoic acid, trimethylolpropane and acetone, stirring evenly, adding isophorone diisocyanate and triphenylmethane triisocyanate after the temperature reaches 68-70°C, dropping a tin catalyst, stirring for 3-4 hours, and obtaining the isocyanate-terminated polyurethane prepolymer.
6. The method for preparing a nano silver coating for low-temperature and high-humidity thawing equipment according to claim 5, characterized in that: The isocyanate-terminated polyurethane prepolymer comprises the following raw materials, calculated by weight: 13-15 parts of polyethylene glycol, 3-4 parts of castor oil, 2-3 parts of dihydroxybenzoic acid, 2-3 parts of trimethylolpropane, 25-30 parts of acetone, 10-12 parts of isophorone diisocyanate, 4-6 parts of triphenylmethane triisocyanate, and 0.2-0.4 parts of a tin catalyst.
7. The method for preparing a nano silver coating for low-temperature and high-humidity thawing equipment according to claim 1, characterized in that: The preparation of the polyurethane acrylate comprises the following steps: Take the isocyanate-terminated polyurethane prepolymer, raise the temperature to 60-70°C, add hydroxyethyl methacrylate, stir and react until the -NCO content reaches the theoretical end point, stop the reaction, and remove the solvent by rotary evaporation to obtain polyurethane acrylate; The polyurethane acrylate comprises the following raw materials, calculated by weight: 10 to 15 parts of isocyanate-terminated polyurethane prepolymer and 2 to 3 parts of hydroxyethyl methacrylate.
8. The method for preparing a nano silver coating for low-temperature and high-humidity thawing equipment according to claim 1, characterized in that: The preparation of the graphite-supported silver nanowires comprises the following steps: Take graphite, add ethanol, and disperse it evenly by ultrasonication to obtain a graphite dispersion; take the graphite dispersion, heat it to 150-160°C and keep it warm for 10-15 minutes, add polyvinyl pyrrolidone, heat it for 20-30 minutes, add 0.2mmol / L CuCl2 aqueous solution and 0.2mmol / L AgNO3 aqueous solution, stir it for 5-8 minutes, add 3mmol / L AgNO3 aqueous solution, stir it for 20-30 minutes, filter, wash and dry it to obtain graphite-loaded silver nanowires; The graphite dispersion includes the following raw materials, calculated by weight: 2 to 3 parts of graphite and 150 to 200 parts of ethanol; the graphite-loaded nanosilver wires include the following raw materials, calculated by weight: 100 parts of graphite dispersion, 2 to 3 parts of polyvinyl pyrrolidone, 10 to 12 parts of 0.2 mmol / L CuCl2 aqueous solution, 20 to 25 parts of 0.2 mmol / L AgNO3 aqueous solution, and 10 to 15 parts of 3 mmol / L AgNO3 aqueous solution.
9. The method for preparing a nano silver coating for low-temperature and high-humidity thawing equipment according to claim 1, characterized in that: The curing conditions of the nano silver coating are: temperature 45-55°C, 800-1000 mj / cm 2 Expose to ultraviolet light until film is formed.
10. The nano silver coating prepared according to the method for preparing a nano silver coating for low-temperature and high-humidity thawing equipment according to any one of claims 1 to 9.
Citation Information
Patent Citations
Vacuum-plating ultraviolet curing intermediate paint
CN102206436A
Anti-wear vinyl silicone oil modified acrylic emulsion and preparation method thereof
CN109111554A
Preparation method of UV conductive ink of inorganic dispersant modified silver nanowires
CN113480893A
Hydrolysis-resistant storage-stable water-based alkyd resin coating and preparation method thereof
CN113773729A
Anti-slip and anti-falling perfume bottle and preparation method thereof
CN117384459A